Dry pathways and flowing water within culverts jointly promote crossings by carnivore mammals - Craveiro, João (2021)
Roads are linear infrastructures causing high wildlife mortality. Transportation administrations make large investments on mitigation measures to promote safe road crossings by wildlife. Yet, many roads worldwide rely on culverts as the only passages available for fauna even though they were primarily designed to drain water. Indeed, culverts inundate repeatedly, becoming unavailable to most terrestrial fauna during rainy periods. How much this pervasive flooding affects the crossing of culverts by animals remains unknown. This was addressed in an Action of the LIFELINES project (LIFE14 NAT/PT/001081) focusing on the effects of flooding on mammal crossings. In this context, we covered wet and dry seasons along three national roads in the Alentejo region of southern Portugal, to understand if water-related variables (pathway dry width, water cover, and water depth at crossing time) explain differences in the probability of crossing by medium-sized carnivore mammals and if they are correlated with crossing frequency too. We also wonder whether crossing frequencies would be similar between seasons. We hypothesized that carnivores would overall be less likely to cross and cross less often if the culvert had more water (e.g., narrower dry width), possibly leading to more crossings during the dry season. To assess carnivore crossings, we installed track stations inside 30 drainage culverts (out of 307 crossing passages inventoried), which were spaced 2 km apart along the roads. According to the degree of flooding, the plates were raised using roof tiles and stone blocks up to 10 cm or lowered when the culvert was drier. We also developed an evaluation to distinguish animal visits to the culverts from actual crossings and used only the latter for analysis. To further validate our crossing assessments using track stations, we concurrently used infrared cameras in 20 of the culverts. We recorded 1211 crossings, averaging 0.96 and 1.01 crossings/day over the wet season and dry season, respectively. Egyptian mongoose (Herpestes ichneumon), European badger (Meles meles), Common genet (Genetta genetta) and Eurasian otter (Lutra lutra) were the species that crossed most. Except for otters, as expected, greater dry widths increased both the probability and the frequency of crossings through the culverts. Dry width was the only significant predictor for the probability of crossing by genets. From our model for all species combined, enlarging the dry width from 0.5mup to 1 or 2m increased the probability of crossing by ~11% and~35%, respectively. Surprisingly, the presence of flowing water within the culverts also correlated positively with crossings by most species in addition to the positive effect of the increase in dry width. For the species most represented in our study, the Egyptian mongoose, contrary to expectations, was more likely to cross culverts when they had ~30 to ~60 % water cover than when they were drier. The significance of the difference in crossing frequencies between wet and dry seasons varied with the species. Broadly, our results show that flooding degree and dry width together influence the probability and frequency of crossing by these carnivore species.